Missed on Imaging, Found on Laparoscopy: A Case of Primary Infertility (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Infertility is a significant global reproductive health concern, affecting approximately 10–15% of couples, with female factors contributing to nearly half of cases. Although imaging modalities such as ultrasonography and hysterosalpingography (HSG) are widely used as first-line diagnostic tools, they may fail to detect subtle uterine anomalies, tubal pathologies, or peritoneal conditions. As a result, a considerable number of patients are categorized under unexplained infertility. Diagnostic hysterolaparoscopy has emerged as gold standard for comprehensive infertility evaluation, as it allows direct visualization of pelvic organs along with opportunity for simultaneous therapeutic intervention.Aim & Objective: To emphasize the diagnostic value of laparoscopy in identifying pelvic and uterine abnormalities that are not detected by conventional imaging techniques in patients with long-standing primary infertility.Case Presentation: This case involves a 30-year-old woman presenting with primary infertility of eight years’ duration. Preliminary investigations, including hormonal assays, transvaginal ultrasonography, and partner semen analysis, were within normal limits. HSG findings suggested bilateral cornual block. To further evaluate the underlying cause, the patient underwent diagnostic hysterolaparoscopy with chromopertubation under anesthesia.Results: Hysteroscopic examination was inconclusive due to a markedly narrow (pinpoint) internal os, which limited proper uterine cavity assessment. However, laparoscopic evaluation revealed a bicornuate uterus with a non-communicating rudimentary horn-an anomaly not identified in previous imaging studies. Additionally, intra-abdominal findings raised suspicion of abdominal tuberculosis. These combined findings led to a significant revision of the initial diagnosis and influenced subsequent management planning.Conclusion: Diagnostic laparoscopy plays a pivotal role in uncovering hidden pelvic and uterine abnormalities in infertility cases where non-invasive modalities yield inconclusive or misleading results. Early implementation of hysterolaparoscopy, particularly in long-standing infertility, enhances diagnostic accuracy, enables timely intervention, supports more effective, individualized treatment strategies.